Analysis of Twitter Conversation on COVID-19 Pandemic in Africa 2019-2020 - Shamsudeen Ademola Sanni; Neema Rajabu; Aliyu Olugbenga Yusuf; Ntombikayise Nomsa Mathabela; Lasisi Kamoru Alamu (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Communication about COVID-19 pandemic has a huge impact on coordination, control and mitigation efforts against the disease. Patterns and trends of COVID-19 pandemic conversations amongst African tweeps between the year 2019 and 2020 was studied. This study aimed to determine the impact of Twitter COVID-19 information dissemination on attitudes, behaviour and decision making during the pandemic.Subjects and Method: This was a cohort study with combined quantitative and qualitative approach. This study was conducted in Africa, from December 2019 to December 2020. The quantitative approach was founded on data mining and data analytics research approach, applying measurements in terms of counts, numbers and frequencies while qualitative approach was founded on Natural Language Processing (NPL) algorithm to extract themes/topics and further applying sentiment analysis to a body of large textual data.Results: A total number of 24,251 tweets was recorded, out of which 9, 016 (37.2%) of the tweets were positive, indicating positive attitude towards COVID-19 related information, control, treatment and regulations. A number of 7, 024 (29%) of tweets were considered neutral, indicating a neutral opinion on conversations related to COVID-19, while 8, 211 (33.9%) were considered negative tweets. South Africa is the most frequently used word and frequently used hashtag followed by Nigeria. Result further revealed four clear topics of discussion which are: a) Africa coronavirus, b) First sub-Saharan pandemic variant, c) Total number of confirmed new deaths, and d) COVID-19 cases in Africa. Besides, it was observed that most health authorities and health partners in Africa are not actively participating on Twitter.Conclusion: Health information dissemination on social media must be moderated through censorship, otherwise fake news and misinformation would persist to aggravate the spread of diseases and cause deaths. In order to protect the public against false information, public health institutions, governments and partners in health should establish an active presence on social media to share factual information, and timely debunk misinformation. Keywords: Africa, COVID-19, twitter Conversation, social media, sentiment AnalysisCorrespondence: Sanni Shamsudeen Ademola. Department of Computer Science, Faculty of Science and Engineering, University of Eswatini, Private Bag 4, Matsapha, Manzini, Kingdom of Eswatini. Email: sanniade01@gmail.com. Mobile: +26876241155/79241155Journal of Health Promotion and Behavior (2021), 06(04): 272-283DOI: https://doi.org/10.26911/thejhpb.2021.06.04.02